LA SOCIEDAD DE LA DESCONFIANZA - Davovich, Egon (La Sociología en sus Escenarios, 2012)
Abstract.The majority of the social organizations, has like main intention, to maximize the benefits, to diminish the problems and to promote the participation of their members, through the generation of confidence networks. The political organizations take pains and plan solutions for the four (4) common and appellants existing problems in the modern society: delinquency, health, use and education; and they base the success of its proposals on the objectives reached in these matters. But it is understood that to obtain advances, they are these social or economic ones, the leaders require of the confidence, commitment and loyalty of those for those who design and construct the policies. Any error becomes a questioning to the capacity to govern. To construct to the equation confidence, commitment and loyalty, is imperative. Resumen.La mayoría de las organizaciones sociales, tienen como propósito principal, maximizar los beneficios, disminuir los problemas y promover la participación de sus miembros, a través de la generación de redes de confianza. Las organizaciones políticas se esmeran y planifican soluciones para los cuatro (4) comunes y recurrentes problemas existentes en la sociedad moderna: delincuencia, salud, empleo y educación; y basan el éxito de sus propuestas en los objetivos alcanzados en estas materias. Pero se entiende que para lograr avances, sean éstos sociales o económicos, los dirigentes requieren de la confianza, compromiso y lealtad de aquéllos para quienes se diseñan y construyen las políticas. Cualquier desacierto se convierte en un cuestionamiento a la capacidad de gobernar. Construir la ecuación confianza, compromiso y lealtad, es imperativo.